Hematological Profile in Patients with Dengue Fever: Report of 47 Patients in 2010 - MUHAMMAD ONEEB SALEEMI, ATIYA MAHBOOB, ASMA MUNIR, MONA AZIZ (Journal of Fatima Jinnah Medical University, 2018)
Background: Dengue fever is one of the major causes of morbidity and mortality in tropical and sub-tropical countries. The routine haematological examination is an important investigation for the diagnosis and proper management of such patients. Objective: To evaluate haematological changes in patients with dengue fever. Design: Prospective, follow-up study. Place and duration of study: Department of Medicine, Shaikh Zayed Federal Postgraduate Medical Institute, Lahore from 3rd Oct 2010 to 20th Nov 2010. Patients and Methods: Forty-seven serologically confirmed, admitted cases were evaluated for age, gender and haematological changes. Results: Forty-seven out of 59 patients had positive serology for dengue fever. Male to female ratio was 1.09:1. Their ages ranged from 5 to 68 years with a mean of 31.3±15.39 years. Analysis of hematological data revealed normal levels of haematocrit, total leukocyte and platelet counts in 81 %, 36.2 % and 6.4 % patient respectively. Serial analysis of data over seven days showed marked improvement of platelet count after second day of admission. Conclusion: Thrombocytopenia is a consistent finding in DF.